English consonant clusters - Sanderson, P. (Peter), 1925- (Commonwealth and international library. Pergamon Oxford English series for overseas students., 1966)
English Consonant Clusters focuses on the phonetic transcription, stress, and tone of English consonants and consonant clusters. The topics discussed include the phonetic alphabets; intrusive consonant; teaching consonants; study of textbook practice; pursuit of the phoneme; individual consonant studies; weak consonants; and English consonant clusters. In order to fully make use of this book, readers are expected to possess basic knowledge of one or two systems of phonetic transcription, phonemes of English, stress, tone, and other phonetic matters. This publication is intended for English tea.